Pengaruh Periklanan Islami terhadap Keputusan Pembelian Produk Shampoo Hijab Sunsilk Clean And Fresh pada Mahasiswi Universitas Islam Riau - Zulkifli Zulkifli; Boy Syamsul Bakhri; Maysuri Maysuri; Ficha Melina (Journal of Management and Bussines (JOMB), 2019)
The purpose of the research was to determine the effect of Islamic advertising on purchasing decision for Clean and Fresh Sunsilk Hijab Shampoo. The subject of this research was students of Riau Islamic University. While the object of this study was the effect of Islamic advertising on purchasing decision for Clean and Fresh Sunsilk Hijab Shampoo. The data sources used in this study were primary data and secondary data. The sampling technique used was proportional stratified random sampling, while the data collection technique used was a questionnaire. To analyze the data, quantitative descriptive method was used. In analyzing quantitative data, simple linear regression analysis was used where the calculation process used SPSS for windows version 23. The sample of this study was 96 people. The result of the research showed Islamic advertising on purchasing decision for Clean and Fresh Sunsilk Hijab Shampoo had a strong or high relationship, this was related to the correlation coeffisien which was 0.763. The result of the research, the result of partial test related to the significant influence between Islamic advertising on purchasing decisions for Clean and Fresh Sunsilk Hijab Shampoo, it was known from the value of tcount (11.452) which was bigger than t table (1.661). Conclusion, there was a significant effect between Islamic advertising on purchasing decisions for clean and fresh sunsilk hijab Shampoo to students of Riau Islamic University Keywords: Islamic Advertising, Purchasing Decision